Plasmodium vivax: restricted tropism and rapid remodelling of CD71 positive reticulocytes. - Malleret, B; Li, A; Zhang, R; Tan, K; Suwanarusk, R; Claser, C; Cho, J; Koh, E; Chu, C; Pukrittayakamee, S; Ng, M; Ginhoux, F; et al. (2014)
Plasmodium vivax merozoites only invade reticulocytes, a minor though heterogeneous population of red blood cell precursors that can be graded by levels of transferrin receptor (CD71) expression. The development of a protocol that allows sorting reticulocytes into defined developmental stages and a robust ex vivo P. vivax invasion assay, has made it possible for the first time to investigate the fine scale invasion preference of P. vivax merozoites. Surprisingly, it was the immature reticulocytes (CD71(+)) that are generally restricted to the bone marrow that were preferentially invaded, whereas older reticulocytes (CD71(-)) principally found in the peripheral blood were rarely invaded. Invasion assays based on the CD71(+) reticulocyte fraction revealed substantial post-invasion modification. Thus, 3-6 hours after invasion the initially biomechanically rigid CD71(+) reticulocytes convert into a highly deformable CD71(-) infected red blood cell devoid of host reticular matter, a process that normally spans 24 hours for uninfected reticulocytes. Concurrent with these changes, clathrin pits disappear by 3 hours post-invasion, replaced by distinctive caveolae nanostructures. These two hitherto unsuspected features of P. vivax invasion, a narrow preference for immature reticulocytes and a rapid remodelling of the host cell, provide important insights pertinent to the pathobiology of the P. vivax infection.